The value of Vigofac and Terramycin B12 supplement Bi-Con TM-10 antibiotic in the rations of fattening pigs on alfalfa pasture - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Vigofac, put out by Chas. Pfizer & Co., is another additive that has recently come into the pig-feeding arena. It was thought desirable to compare it with antibiotics for fattening pigs on pasture. In this test four lots of spring pigs were self-fed free choice a basal ration of shelled corn and a mixed protein supplement on alfalfa pasture. The mixed protein supplement was made up of 4 parts tankage, 4 parts soybean meal, 1 part linseed meal, and 1 part alfalfa meal. Lot 1 pigs received no Vigofac or antibiotic. They were self-fed the basal ration of a mixed protein supplement and shelled corn. Lot 2 pigs were self-fed shelled corn and a mixed protein supplement to which had been added Vigofac at the rato of 27 pounds to the ton.
Keywords: Swine; Vigofac; Terramycin B12; Alfalfa